2016
DOI: 10.15171/ijhpm.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

Digital Direct-to-Consumer Advertising: A Perfect Storm of Rapid Evolution and Stagnant Regulation Comment on "Trouble Spots in Online Direct-to-Consumer Prescription Drug Promotion: A Content Analysis of FDA Warning Letters"

Abstract: The adoption and use of digital forms of direct-to-consumer advertising (also known as "eDTCA") is on the rise. At the same time, the universe of eDTCA is expanding, as technology on Internet-based platforms continues to evolve, from static websites, to social media, and nearly ubiquitous use of mobile devices. However, little is known about how this unique form of pharmaceutical marketing impacts consumer behavior, public health, and overall healthcare utilization. The study by Kim analyzing US Food and Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Research into US pharmaceutical advertising has noted the difficulty of regulating direct marketing (Gibson, 2014; Henney, 2000; Mackey, 2016; Taylor, Franke, & Maynard, 2000). Gibson (2014) concluded that third party oversight and industry self-regulation are important in regulating direct marketing, although gambling industry self-regulation has been criticized (Selin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research into US pharmaceutical advertising has noted the difficulty of regulating direct marketing (Gibson, 2014; Henney, 2000; Mackey, 2016; Taylor, Franke, & Maynard, 2000). Gibson (2014) concluded that third party oversight and industry self-regulation are important in regulating direct marketing, although gambling industry self-regulation has been criticized (Selin, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Past research suggests companies have minimized or obscured such disclosures [ 32 ]. The bigger challenge, however, is whether it is feasible to regulate how pharmaceutical companies control information about their products across new media platforms that they might only indirectly influence or control [ 7 , 12 ]. Obviously pharmaceutical companies should not be expected to police the entire Internet.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of social media and other interactive platforms has only exacerbated concerns related to DTCA leading prominent scholars and health professionals to wonder “...whether regulatory responses by FDA are responsive and adaptive enough to address the inherent challenges faced by a universe of digital and Internet-based forms of DTCA” (p 271 [ 12 ]). Specifically, researchers and health professionals are extremely concerned that companies will market their drugs online in ways that (1) obscure the role companies play in producing drug information, and (2) strategically control user-generated contributions to promote a favorable, one-sided view of a company and its products [ 5 , 8 , 12 ]. A recent content analysis clearly documents how prominently pharmaceutical companies are using Facebook, YouTube, and Twitter for promotional activities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, pharmaceutical companies spent over $6.4 billion to advertise directly to U.S. consumers, using practices that could easily mislead the consumer about the efficacy of their medications and their side effects, or prompt consumers to request medication that is unnecessary. In 2015, the American Medical Association voted to support a ban on direct-to-consumer advertising (Mackey, 2016). The original intent of the FDA's guidelines that allow direct-to-consumer pharmaceutical advertising was to encourage consumers to seek additional information online and elsewhere (Chesnes & Jin, 2016;Horovitz & Appleby, 2017).…”
Section: Th Century Innovationsmentioning
confidence: 99%